You Call This Exemplary? Lessons from an Unsung International Evaluation - Douglas Horton (Journal of MultiDisciplinary Evaluation)
This paper reflects on the role of academic discipline and epistemic community in judging what is an exemplary evaluation. It examines the case of an evaluation that was considered ‘exemplary’ by a panel of program evaluators, but methodologically flawed by evaluators from a different evaluation tradition. The evaluation in question was carried out within an international agricultural research network (known as the CGIAR), with a rich tradition of economic impact assessment. The evaluation was carried out by a team of experienced program evaluators, who attempted to apply accepted good practices in the program evaluation community. The evaluation employed mixed methods and multiple data sources with heavy reliance on triangulated perceptual data. A meta-evaluation led by an experienced program evaluator considered the evaluation to be exemplary. However, within the CGIAR, both the evaluation and the meta-evaluation study were rejected, as methodologically flawed. The paper closes with four propositions related to what is considered an “exemplary evaluation.”